2021
DOI: 10.1002/pon.5689
|View full text |Cite
|
Sign up to set email alerts
|

Social support and siblings of children with cancer: A scoping review

Abstract: Objective Social support is essential in healthy adjustment to life stressors. This scoping review examines how social support has been conceptualized, operationalized, and studied among siblings of children with cancer. Gaps in the current literature are identified, and future research directions are proposed. Methods A rigorous systematic scoping review framework guided our process. Medline, Embase, CINAHL, PsycINFO, and Scopus were searched for literature regarding social support and siblings of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 76 publications
(358 reference statements)
0
16
0
1
Order By: Relevance
“…Although caregivers of hospitalized acute leukemia patients experience negative effects such as financial burden and anxiety and depression during the process of caregiving, caregivers also perceive a sense of illness benefit and growth, such as learning to accept reality, appreciate the meaning of life, cherish the present moment, and have confidence and hope, increased ability to actively learn and caregiving, perceived multiple support from family, friends, and healthcare providers, and health-related cognitive behaviors. e perception of health-related cognitive behaviors improves [13]. Among the three dimensions of the BFS-C scale, the highest score for the personal growth dimension may be related to the following two factors e highest scores on the personal growth dimension of the BFS-C scale may be related to the fact that caregivers are able to self-regulate their negative emotions and have improved self-control; the overall psychological and spiritual growth of the caregiver as the caregiving time increases, as well as the acquisition of knowledge about the disease and caregiving skills.…”
Section: Current Analysis Of the Level Of Disease Benefit Perception ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although caregivers of hospitalized acute leukemia patients experience negative effects such as financial burden and anxiety and depression during the process of caregiving, caregivers also perceive a sense of illness benefit and growth, such as learning to accept reality, appreciate the meaning of life, cherish the present moment, and have confidence and hope, increased ability to actively learn and caregiving, perceived multiple support from family, friends, and healthcare providers, and health-related cognitive behaviors. e perception of health-related cognitive behaviors improves [13]. Among the three dimensions of the BFS-C scale, the highest score for the personal growth dimension may be related to the following two factors e highest scores on the personal growth dimension of the BFS-C scale may be related to the fact that caregivers are able to self-regulate their negative emotions and have improved self-control; the overall psychological and spiritual growth of the caregiver as the caregiving time increases, as well as the acquisition of knowledge about the disease and caregiving skills.…”
Section: Current Analysis Of the Level Of Disease Benefit Perception ...mentioning
confidence: 99%
“…Acute leukemia is a global problem, and according to the International Agency for Acute Leukemia Research (IARC), 22.2 million people are expected to suffer from acute leukemia by 2030 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined siblings’ perspectives of their social support or associations between support and adjustment [ 14 , 15 ]. A recent scoping review suggested that social support is indeed helpful to siblings; however, the most important sources and types of helpful support for siblings of children with cancer remain unclear [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with younger siblings, adolescent siblings may be particularly impacted by these changes resulting in physical, financial, social strains ( Ward et al, 2014 ). The reduced attention they receive from parents and extended family members may result in these adolescent siblings feeling jealous and angry, and needing to compete with their ill sibling ( Prchal and Landolt, 2012 ; McDonald et al, 2015 ; Yang et al, 2016 ; Cheung et al, 2020 ; Wawrzynski et al, 2021 ). These siblings often complain of their parents’ lack of time for them and often experience negative feelings and impaired quality of life ( Cheung et al, 2020 ; Pariseau et al, 2020 ; Wawrzynski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%